Kesiapan Pustakawan Berkolaborasi dengan Profesi Lainnya Mendukung Peningkatan Kapasitas dan Kesejahteraan Masyarakat Pertanian - Riko Bintari Pertamasari; Juznia Andriani; Penny Ismiati Iskak; Ira Dwi Rachmani (Perpustakaan Nasional, 2022)
Indonesian Center for Agricultural Library and Technology Dissemination is known as PUSTAKA has made a breakthrough by providing social inclusion services. The inclusion activity is carried out through collaboration between librarians and other professions. This study aims to determine the readiness of librarians to collaborate with other professions, the barriers to collaboration, and the abilities that librarians must possess to collaborate. The method in this study is a qualitative approach with a case study method. The subject of this study is the librarian at PUSTAKA. We found that: 1) librarians had collaborated with extension workers and felt the benefits of this collaboration; 2) obstacles faced are misscommunication, lack of capital, limited land, and lack of time. These obstacles can be overcome by proper communication and cooperation with other related parties. The collaboration between librarians and other profession is relevant to the dissemination of agricultural innovations. The librarian's skills related to cooperation include communication skills, problem solving skills, adaptability, and emotional intelligence. Based on the results of the study, it can be concluded that librarians and library managers are ready to collaborate with other professions. In future studies, it is necessary to review the librarian within the Ministry of Agriculture along with the models of cooperation that have been implemented.